Legal Protection of the Sustainability of Angus Stone as a Geopark Protected Area in Ternate City - Albugis, Wita; Alting, Husen; Sinay, Siti Barora (CV. Publikasi Indonesia, 2025)
This research explores the sustainable legal control and protection of Angus Stone (Batu Angus) utilization in Ternate City. Angus Stone is a unique geological formation with significant historical, cultural, and scientific value, recognized as part of the Geopark Protected Area and categorized as a national strategic asset. The study aims to analyze the legal mechanisms governing its management, covering planning, implementation, supervision, and monitoring, within the framework of sustainable development. Employing an empirical legal research method, this study focuses on Ternate City through purposive sampling interviews, field observations, documentation, and review of relevant legislation, supported by secondary data from scholarly sources. The findings indicate that current management is regulated by national legal provisions but lacks systematic implementation aligned with sustainable principles. Drawing from Gustav Radbruch’s theory of legal objectives, the research emphasizes the necessity for regulatory structures that are just, orderly, and transparent. These structures must prevent exploitative practices while respecting local wisdom and maximizing community benefits. The study recommends that a successful legal protection framework must incorporate sustainable planning, enforce management practices that align with sustainability standards, and ensure ongoing and effective supervision. Such a framework would not only preserve Angus Stone as a natural heritage but also contribute to the economic, social, and cultural development of Ternate City .